Fashion in poetry: the uses of fiction and otherness - Kempinska, Olga (Farol, 2024)
This article seeks to reflect on the relationship between fashion and fiction. Divided into two parts, the text analyzes the issues of reversibility, subversion, tradition and innovation, proposing to understand the possibilities of fashion in the affirmation of the otherness of the other, also in what concerns gender. The anthropology of fiction and the reflection on inscription and writing constitute the theoretical approaches that guide the interpretation of the poetic texts of different authors: Jean Cocteau, Anton Chekhov, Elfriede Jelinek, Terrance Hayes, Ashley Mace Havird and Ewa Lipska. Often critical of the metaphors of depth, also in what concerns subjective essentialism in its post-romantic aspects, fashion emphasizes surface and convention. Unlike fashion theories, which seek definitions, literary texts emphasize above all their conceptual openness, their indifference to subjective expressive manifestations, and their relationship with play.